The Study of the relationship between ABO blood groups with gastric cancer and its staging - Bayzid Ghaderi; Delir Rostami; Nasrin Daneshkhah; Farshad Sheykhesmaili; Mokhtar Yaghobi; Hamideh Ghaderi (Kurdistan University of Medical Sciences, 2015)
Background and Aim: Gastric cancer is addressed among developing countries as a public health problem. The relationship between ABO blood groups and cancer has been proven years ago. According to various studies, the incidence of gastric cancer is higher in people with blood group type A. In this study, the relationship between ABO blood groups and gastric cancer; staging and tumor subgroups were studied. Materials and Methods: This cross-sectional study was conducted on 100 patients with gastric cancer who were confirmed by histopathology. The relationship between ABO blood groups and staging and type of pathology of the tumor and its gastric adenocarcinoma subtypes including diffuse and intestinal type were studied. Statistical analysis was performed using chi-square test and SPSS software. Findings: The results showed that the incidence of stomach cancer in people with blood group type A is greater. The study showed that there was a significant relationship between blood groups and gastric cancer (p> 0.05). Also, the study showed that there is no significant relationship (p= 0.55) between blood groups and types of tumor subgroup. Moreover, there was no significant relationship between blood group and tumor differentiation (p = 0.12). Conclusion: This study showed that there is a relationship between blood group A and gastric cancer. Considering the higher prevalence of gastric cancer in people with blood group A, identifying and eliminating other risk factors for cancer, is necessary.